The effects of human-wildlife conflict on conservation and development : a case study of Volcanoes National Park, northern Rwanda - Mc Guinness, Shane (Trinity College (Dublin, Ireland). Department of Geography, 2014)
Rising global population pressure and associated increases in demands for natural resources have resulted in heightened pressure on areas containing valued biodiversity. Efforts to assist the development of marginalised communities, however, often contravene measures aimed at the sole conservation of these areas. As such, tension often exists between the aims of conservation and development, preventing equal gains in the two. Inflaming this tension is the interaction between economically marginalised communities and protected fauna, which can result in human-wildlife conflict (HWC) of varying forms, including disease transmission, livestock depredation, crop loss and property damage. As humans can be seen as the common denominator of HWC, social and political considerations must be made at both proximal and distal levels: HWC is not merely a quantifiable ecological problem. This study has focussed on one form of HWC, crop raiding, and the constraints imposed by it on conservation and human development efforts, using a forested protected area in tropical Africa as case study.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin